Hubungan Kemandirian Ekonomi dengan Kualitas Hidup Lansia - Parmadi Sigit Purnomo; Sri Setyowati; Istika Dwi Kusumaningrum (Jurnal Indonesia Sehat, 2022)
The elderly are a group of people who experience a decrease in physical limitations due to the aging process, but some of the elderly are still able to carry out independent activities according to their abilities. Economic independence is one of the factors that can affect a person's quality of life. The purpose of this study was to determine the relationship between economic independence and quality of life in the elderly. The type of research used in this research is non-experimental research with a correlational study design that uses a cross sectional approach. The population in this study were all the elderly who joined the Posyandu Matahari Kepek Timbulharjo Sewon Bantul Yogyakarta as many as 32 elderly people. The sampling technique used was total sampling so that a sample of 32 elderly people was obtained. This research activity was conducted at the Elderly Posyandu Matahari Kepek Timbulharjo Sewon Bantul Yogykarata, in September 2021. The variables in this study were economic independence in the elderly and quality of life in the elderly. The instruments used are the economic independence questionnaire and the Hyper Text Query Language (HTQL) questionnaire from sf-36. The statistical test that will be used is the Kendall-Tau correlation formula. The results of this study indicate that the majority of respondents are men with the age of entering the elderly category and do not work so they have no income. The majority of respondents live with other family members. Economically, the majority of respondents fall into the category of not being independent in their economy, but the quality of life is still quite adequate. In this study also analyze the relationship between research variables. Test analysis using the Kendal tau correlation. The results of the analysis test showed a p-value of 0.059 < 0.005. The conclusion shows that there is no relationship between economic independence and the quality of life of the elderly.